Analysis, design and experiment of continuous isolation structure with Local Quasi-Zero-Stiffness property by magnetic interaction. (November 2019) - Sun, Xiuting; Wang, Feng; Xu, Jian
Abstract: In this study, magnetic interaction is applied to a continuous structure as local negative-stiffness components to improve the vibration isolation performances and to extend the vibration isolation band. According to the theory of electromagnetic fields, the mechanical model of interaction force is established. This model is used to discover that the magnetic interaction can induce the negative stiffness property locally using appropriate structural parameters. Because different structural parameters of the magnets can increase the negative stiffness strength with different effects, the parameters of the continuous beam and magnets are adjusted for the design of accurate zero stiffness property locally. Then, the relationship between structural parameters and effective isolation bandwidth is established by deriving the solution of steady state around zero equilibrium. As the nonlinearity and zero-stiffness property only occur locally around zero equilibrium and the system displays the positive-stiffness property for large vibration amplitudes, the effective isolation band is significantly extended, and the amplitude–frequency curve is similar to the linear system at resonance. The relevant experiments demonstrate the remarkable tuning characteristic of structural parameters of magnets on the isolation features, which realize the improvement of isolation/protection effectiveness for time-lasting excitation at a low frequency. This study not only demonstrates the advantages of nonlinearity induced by local magnetic interaction on the improvement of isolation performances but also realizes a continuous structure with local quasi-zero stiffness applied in fields of low-frequency engineering structures. Highlights: Realizing adjustable negative stiffness by magnetic interaction. Utilizing local property of magnetic force to realize quasi-zero-stiffness property. Building the relation between structural parameters and effective isolation band. Assembling the relevant experiment of continuous structure under magnetic field.